Pengaruh Karakter, Pola Asuh dan Masalah Orangtua Terhadap Perilaku Anak Di Sekolah - Dewi, Chandra (Al-Fikru: Jurnal Ilmiah, 2021)
Discussing about children, is an interesting discussion for parents and educators because behind it all there are unique facts relating to children’s behavior and their correlation with children’s problems. What happens at home or at school. Families, especially mothers are the first madrasas children before studying in formal and non-formal educational institutions, so the family must have a greater role in terms of being responsible for educating children. The role of parents must be able to meet the psychological and physical needs of a child so that the child as the holder of the line can be a person that his parents can be proud of. Good interaction between parents and children can create a conducive relationship and will greatly affect children’s development in terms of cognitive and emotional. The problem is, has this matter become an important priority for parents? This is where the author feels the need to do research because many see the fact that it happens precisely the attitudes and behavior of parents become a problem trigger for children in behaving in their social environment, especially the school environment. The author would like to see how much "Influence of Character, Parenting Style and Problems of Parents on Children’s Behavior in Schools" so they can provide input to parents and educators how to overcome these problems because children are the future assets of parents. Children are also the assets of the nation which is a new generation and human resources that have an important role as the successor to the ideals of the nation’s struggle. This is background, the writer who also acts as a parent and educator feels that he has responsibility for the future of the nation and state in the future in the hands of our children. The better the child’s personality, the better the nation’s future. Conversely, the bad personality of the child will also be bad for the life of the nation to come.for children in behaving in their social environment, especially the school environment. The author would like to see how much "Problems of Parents’ Influence on Child Behavior in Schools" so they can provide input to parents and educators how to overcome these problems because children are the future assets of parents. Children are also the assets of the nation which is a new generation and human resources that have an important role as the successor to the ideals of the nation’s struggle. With this background, the writer who also acts as a parent and educator feels that he has responsibility for the future of the nation and state in the future in the hands of our children. The better the child’s personality, the better the nation’s future. Conversely, the bad personality of the child will also be bad for the life of the nation to come..